Influence of void content and morphology on the creep behavior on glass/epoxy composites - Alves, Fillip Cortat [UNESP]; Monticeli, Francisco Maciel [UNESP]; Neves, Roberta Motta; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Ornaghi, Heitor Luiz (Elsevier, 2021)
This study aimed to evaluate the dynamic mechanical properties and the creep behavior of glass/epoxy composites containing different void contents. A 3D reconstruction using X-ray microtomography (MCT) was done to determine void content, position, and morphology. Moreover, dynamic mechanical analysis over a wide temperature range and creep tests using different temperatures (from 30 °C to 210 °C) and stress levels (1, 5, and 10 MPa) were conducted. It was found that the void content interfered with the stress transferring, noted by a decrease in the storage modulus in the glassy region and by a higher creep deformation. Moreover, as the composites pass through the glass transition region, a more abrupt decay is observed due to higher dissipation energy in a shorter time. The trend of creep behavior by temperature and stress level is equally affected by the void content and morphology.
Keywords: Creep behavior; Dynamic mechanical analysis; Void content